Atypical presentation of aural tuberculosis with complication. (9th March 2018) - Singh, Anup; Irugu, David Victor Kumar; Verma, Hitesh; Thakar, Alok
Abstract : Tuberculosis involving mastoid and ear is an uncommon entity presenting with myriads of non-specific features and difficult to diagnose, being a paucibacillary condition. The involvement of otomastoid compartment is hypothesised to be of haematogenous origin. Rarely it can spread directly via tympanic membrane perforation or via reflux through eustachian tube. The usual picture of presentation tends to be one of indolent ear infection not responsive to usual antibiotic treatment and symptomatology being out of proportion to examination findings. We present a case of aural tuberculosis presenting with zygomatic and Bezold abscess without other symptoms, and the usefulness of GeneXpert test in mycobacterial detection in such paucibacillary conditions.